Nasal Dilators (Breathe Right Strips and NoZovent) for Snoring and OSA: A Systematic Review and Meta-Analysis. (13th December 2016) - Camacho, Macario; Malu, Omojo O.; Kram, Yoseph A.; Nigam, Gaurav; Riaz, Muhammad; Song, Sungjin A.; Tolisano, Anthony M.; Kushida, Clete A.
Abstract : Objective . To systematically review the international literature for studies evaluating internal (NoZovent) and external (Breathe Right Strips) nasal dilators as treatment for obstructive sleep apnea (OSA). Study Design . Systematic review with meta-analysis. Methods . Four databases, including PubMed/MEDLINE, were searched through September 29, 2016. Results . One-hundred twelve studies were screened, fifty-eight studies were reviewed, and fourteen studies met criteria. In 147 patients, the apnea-hypopnea index (AHI) was reported, and there was an improvement from a mean ± standard deviation (M ± SD) of 28.7 ± 24.0 to 27.4 ± 23.3 events/hr, p value 0.64. There was no significant change in AHI, lowest oxygen saturation, or snoring index in OSA patients when using nasal dilators. However, a subanalysis demonstrated a slight reduction in apnea index (AI) with internal nasal dilators (decrease by 4.87 events/hr) versus minimal change for external nasal dilators (increase by 0.64 events/hr). Conclusion . Although nasal dilators have demonstrated improved nasal breathing, they have not shown improvement in obstructive sleep apnea outcomes, with the exception of mild improvement in apnea index when internal nasal dilators were used.